Radioprotective effect of Date syrup on radiation- induced damage in Rats - Shimaa M. Abou-Zeid (Nature Portfolio, 2018)
Abstract Ionizing radiation has cytotoxic and genotoxic effects caused mainly by the oxidative damage induced by free radical release. The need for radioprotectives is increasing to protect normal tissues during radiotherapy. In the present study, we investigated the radioprotective effect of Date syrup in rats subjected to whole body radiation at 6 Gy through biochemical, molecular and histopathological analysis. Significant elevations were recorded in the activities of serum ALT, AST, ALP and LDH and in the levels of all lipid profiles parameters, while the level of HDL-C was reduced. The concentration of liver MDA was elevated with depletion of hepatic glutathione (GSH) and catalase. DNA damage was evidenced by increased DNA strand breakage and DNA-protein crosslinks. Significant elevations were observed in the expression of liver TNF-α and serum activity of matrix metalloproteinase (MMP-9). Pretreatment of rats with Date syrup ameliorated the tissue damage induced by radiation as evidenced by the improvement of liver function, antioxidant status and reduction of DNA damage. Besides, liver TNF-α expression and serum MMP-9 activity were reduced. In conclusion, Date syrup could alleviate the toxic effects of ionizing radiation and thus is useful as a radioprotective in radiotherapy regimen.